PENGARUH KETERLIBATAN ORANG TUA TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA KELAS VIII DI SMP NEGERI 1 SINGKEP PESISIR - Selfia Santika; Isfarida; Rahayu Mega Sari (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2025)
This study aims to examine the influence of parentalinvolvement on the learning motivation of eighth-grade students atSMP Negeri 1 Singkep Pesisir. The research method used isquantitative, employing Product Moment analysis. Data werecollected through questionnaires distributed to 48 students and 48parents at SMPN 1 Singkep Pesisir. The object of this research isstudents' learning motivation. Data analysis methods includevalidity testing, reliability testing, and correlation analysis. Theresults indicate a significant influence between parentalinvolvement and students' learning motivation. The ProductMoment correlation value between variable X (parentalinvolvement) and variable Y (students' learning motivation) is0.739. This reflects a strong degree of influence, as the PearsonCorrelation falls within the range of 0.60–0.799. Therefore, theresearch hypothesis is accepted, and it can be concluded thatparental involvement significantly enhances the learningmotivation of eighth-grade students at SMP Negeri 1 SingkepPesisir. This suggests that parental support helps students feelmore motivated in their studies.